Effect of Financial Literacy and Peers on Student Saving Behavior: The Mediating Role of Self-Control - Salsabila Mona Odelia; Muhadjir Anwar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to determine the effect of financial literacy and peers on the saving behavior of students at State Universities in Surabaya through self-control. Methodology: A quantitative approach was used with 258 respondents from the Faculty of Economics and Business of a state university in Surabaya, obtained through stratified random sampling. Data were collected via online questionnaires and analyzed using Partial Least Squares-SEM (SmartPLS 4.0). Results: Financial literacy (β = 0.160) and peers (β = 0.252) have a positive and significant influence on saving behavior. Moreover, self-control significantly mediates the relationship between financial literacy and peers on saving behavior (β = 0.111). The model demonstrates moderate explanatory power, with R² values of 0.270 for saving behavior and 0.244 for self-control. Findings: The findings confirm that both financial literacy and peer influence are critical determinants of saving behavior, with self-control serving as a key mediating mechanism that strengthens these relationships. Novelty & Originality: This study contributes to the literature by integrating psychological and social factors in explaining saving behavior. Its originality adds a regional context by focusing on economics and business students in Surabaya, representing a group that is financially literate and knowledgeable, which has been underexplored in prior research. Conclusions: Expanding the research scope by involving students from private universities or conducting comparative studies between cities can provide new insights into differences in socioeconomic contexts. Type of Paper: This paper is a research article.